Depth-Resolved Variations of Cultivable Bacteria and Their Extracellular Enzymes in the Water Column of the New Britain Trench - Liu, Qianfeng; Fang, Jiasong; Li, Jiangtao; Zhang, Li; Xie, Bin-Bin; Chen, Xiu-Lan; Zhang, Yu-Zhong (Frontiers in Microbiology, 2018)
Marine microorganisms and their extracellular enzymes (ECEs) play an important role in the remineralization of organic material by hydrolyzing high-molecular-weight substrates to sizes sufficiently small to be transported through cell membrane, yet the diversity of the enzyme-producing bacteria and the types of ECEs involved in the degradation process are largely unknown. In this work, we investigated the diversity of cultivable bacteria and their ECEs and the potential activities of aminopeptidase in the water column at eight different depths of the New Britain Trench. There was a great diversity of cultivable bacteria and ECEs, and depth appears an important driver of the diversity. The 16S rRNA sequence analysis revealed that the cultivable bacteria were affiliated mostly with the phyla Proteobacteria and Actinobacteria, and the predominant genera were Pseudoalteromonas (62.7%) and Halomonas (17.3%). Moreover, 70.7% of the isolates were found to produce hydrolytic zone on casein and gelatin plates, in which Pseudoalteromonas was the predominant group, exhibiting relatively high protease production. Inhibitor analysis showed that the extracellular proteases from the isolated bacteria were serine proteases in the surface water and metalloproteases in the deep water. Meanwhile, the Vmax and Km of aminopeptidase exhibited a maximum in the surface water and low values in the deep bathy- and abyssopelagic water, indicating lower rates of hydrolysis and higher substrate affinity in the deeper waters. These results shed new insights into the diversity of the cultivable bacteria and bacterial ECEs and their likely biogeochemical functions in the trench environment.